E-TRANSFORMATION IN THE SRI LANKAN BANKING INDUSTRY: DRIVERS OF SUCCESS VS BARRIERS TO SUCCESS - Selvarajan, P.; Ranasinghe, B.; Munidasa, D. (IDM Nations Campus, Colombo, Sri Lanka, 2012)
This research study aims to identify the drivers of and barriers to e-transformation success between the public and private sector banks in Sri Lanka. For this purpose two public sector and two private sector banks have been selected based on judgement sampling method. A mixed method approach is adopted by incorporating the quantitative as well as qualitative case study methodologies. This paper focuses on the quantitative method by using the Statistical Package for Social sciences (SPSS) version 16.0. A non-parametric measure of correlation (Spearman’s correlation) has been used. The findings indicate that there are internal and external drivers of and barriers to success of e-transformation in the public and private sector banks. However the support and involvement of each level of management are inevitable factors for this achievement in these banks.
Keywords: Barriers to success; Drivers of success; E-transformation; Private sector banks; Public sector banks